(2358) proposal to conserve the name bartramia curvata (philonotis curvata) against b. fontanoides (p. fontanoides) (bryophyta) - Jimenez, Maria Soledad (2015)
As the name P. fontanoides has scarcely been used and insufficiently known since its description, and in order to avoid disadvantageous nomenclatural changes (Art. 14.1 of the ICN, McNeill & al. in Regnum Veg. 154. 2012) conserving the name B. curvata,the basionym of P. curvata, against B. fontanoides, the basionym of P. fontanoides, as is here proposed, seems desirable. If this proposal is declined, the name P. fontanoides would have to replace the widely used P. curvata, which would be highly undesirable.